8‐Hydroxyquinoline‐Methionine Mixed Ligands Metal Complexes: Preparation and Their Antioxidant Activity. Issue 11 (18th March 2019) - Qamar, Noshab; Sultan, Hira; Khan, Khalid Mohammed; Azmat, Rafia; Naz, Raheela; Hameed, Abdul; Lateef, Mehreen
Abstract: The purpose of this investigation is to synthesize mixed ligand complexes of first, second, and third row transition metals including Cr (III), Mn (II), Fe (III), Co (II), Ni (II), Cu (II), Zn (II), Cd (II) and Pb (II) with L1 = 8‐hydroxyquinoline and L2 = DL‐methionine. Newly synthesized metal complexes have been characterized by UV‐Visible, IR, mass spectrometry and micro‐analytical techniques such as conductance measurement, elemental analysis, and melting point. Synthetic mixed complexes were also screened for antioxidant activity. Abstract : Transition metals based complexes of mixed ligands containing O/N donor atoms were synthesized and characterized by UV‐Visible, IR, mass spectrometry and micro‐analytical techniques. The synthetic complexes were then screened for antioxidant activity.